Dentistry Faculty, Response in Dental Clinics From the perspective of students - E Rouhollahpour-Ahangar (Babol University of Medical Sciences, 2019)
BACKGROUND AND OBJECTIVE: Faculty members are an important member of higher education and have an important role to play in achieving educational goals. Therefore, their interaction with learners is important, such as dental training clinics. The purpose of this study was to evaluate the responsiveness of faculty members of dental school in Babol University of Medical Sciences. METHODS: This study was performed on 89 dental students trained in the clinics of Babol University of Medical Sciences in 2019. Data collection tool was a researcher-made questionnaire using valid scientific sources, including demographic characteristics, and 18 questions about how teachers and students responded on Likert 5 (i.e. excellent to very poor). The content validity index and reliability coefficient were 89.2 and 0.85. Data analyzed by SPSS21 software applying T-test and One-way ANOVA less than 0.05 Significance level. FINDINGS: The highest and the lowest accountability percentages in the excellent category were respectively related to the importance of time in the clinic (38.2%) and attention to student activity during the course (10.1%). These percentages in the good category were related to the response to students' questions (43.8%) And trying to teach poor students in clinical work (23.6%). Also, in the moderate class considering students' performance during the course (37.1%) and the importance of proper student dressing (13.5%). There was no significant difference between gender and place of study (P=0.91). The final year students had a lower score for the teachers (P=0.003). Students were more satisfied with oral, maxillofacial radiology teachers (P <0.001). CONCLUSION: Based on the results, it is suggested that the university of medical sciences, authorities implement educational and cultural correspondence for teaching accountability to professors.